Investigation of In-ovo cytogenetic effect of Levofloxacin: Marwa, H. N. and Falah, M. K. AL-Rekabi - N., Marwa H. (The Iraqi Journal of Veterinary Medicine, 2018)
This study was carried out to investigate the cytogenetic effect of Levofloxacin after In-ovo inoculation. Forty eight fertilized eggs were used, divided equally into eight groups and inoculated through shell puncture above air cell with materials in equestion and incubated for two different periods three and seven days. They were assigned as group one and group two 10 µg Levofloxacin, group three and group four 20µg levofloxacin, group five and group six considered positive control 0.05 µg Mitomycin-C, group seven and group eight (Phosphate Buffer Saline) considered negative control groups. All eggs from in-ovo experiments were subjected to cytogenetic tests, such as Mitotic Index, Replicative Index and Sister Chromatid exchange. Eighty fertilized eggs were handled with the same manner of in-ovo inoculation and used for calculation Hatchability index and weekly body weight. The results revealed significant (P˂0.05) increases in Mitotic Index and Replicative Index of all groups treated with levofloxacin compared to positive control, but there were significant (P˂0.05) decreases compared to control negative. There were no significant changes in Sister Chromatid exchange of all treated levofloxacin in–ovo. The hatchability index revealed significant (P˂0.05) decreases in group three which was inoculated 20 µg levofloxacin after three days of incubation compared to all Levofloxacin treated groups and both positive and negative control groups. In conclusion, levofloxacin in–ovo inoculation has no substantial cytogenetic effects.